The Effect of Stad Model (Student Teams Achievement Division) Assisted by Smart Treasure Promotional Tools on Learning Interest of Grade IV Elementary School Students - Dwi Cahyani, Intan; Malihatul Hawa, Anni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This research is motivated by the lack of innovation in the application of learning models and teaching aids which causes low student interest in learning in the learning process in class IV of SD Negeri Wonorejo 03. The purpose of this study was to determine the effect of the STAD learning model assisted by Smart Treasure teaching aids on student interest in learning. The research method uses a quantitative approach with an experimental method type, namely Quasi Experimental Design with a Non-equivalent Control Group design form. Data collection techniques with non-test techniques include pretest and posttest questionnaires, observation, documentation, and interviews. The data analysis techniques used are the Independent Sample T-Test and Simple Linear Regression. The results of the study showed that: (1) There is a difference in the use of the STAD learning model assisted by Smart Treasure teaching aids on student interest in learning between the experimental class and the control class, as evidenced by the results of the Independent Sample t-test which showed a significance value of 0.003 <0.05. (2) There is an influence in the use of the STAD learning model assisted by Smart Treasure teaching aids on student interest in learning, with the results of the simple linear regression test showing a significance value of 0.000 <0.05. Based on the results of the study, it can be concluded that there is a significant difference between the experimental class and the control class, where the experimental class has an average of 82.8 which is greater than the average of the control class which is 75.3. The use of the STAD learning model assisted by Smart Treasure teaching aids has an effect on students' learning interest by (R Square value of 0.708 or 70.8%) the remaining 29.2% is influenced by other factors.